Pengaruh Kualitas Produk, Daya Tarik Iklan di Medsos dan Persepsi Harga Terhadap Keputusan Pembelian Pada Konsumen Produk Fitarasa Cake Kab. Probolinggo - Eka Sukmawati; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The method used is multiple linear regression. The sampling technique uses the Maholtra formula with the results of calculating 95 samples. In completing this research using SPSS 29 with the help of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, f test and t test. The results of this study indicate that the variables of product quality, advertising attractiveness, and price perceptions influence purchasing decisions simultaneously, product quality variables influence purchasing decisions, and advertising attractiveness variable has no effect on influence purchasing decisions. the price perception variable influences the purchase decision. Keywords: Product Quality, Advertising Attractiveness, Perceived Price on Purchasing Decisions